1905 Ind. Stat. Ann. 231, § 2093 - (:unkn) unknown (My University, 1905)
Ch. 5, art. 4, § 2093: Prohibited brandishing or threatening to use any pistol, dirk, knife, slung-shot, or other deadly or dangerous weapon against any other person. Violators guilty of a misdemeanor, fined not less than one nor more than five hundred dollars and imprisonment not exceeding six months.
Keywords: BRANDISHING